Multiple Diels–Alder Transformations in Linear π-Conjugated Systems - Bedi, Anjan; Gidron, Ori (Synlett, 2019)
π-Conjugated molecules are the active materials in organic electronics, yet the range of available materials is limited by the nontrivial, multistep synthetic process required to obtain long π-conjugated backbones. Here, Diels–Alder cycloaddition and its reactivity and selectivity are evaluated as a means for obtaining long, novel, π-conjugated backbones. Particular attention is paid to the Diels–Alder conjugation products of furans, such as selectively substituted arenes and, potentially, carbon nanoribbons.1 Introduction2 Aromatic Transformations by Diels–Alder Cycloaddition3 The Question of Regioselectivity4 Outlook
Keywords: Diels–Alder cycloaddition; π-conjugated systems; cross-coupling; oligofurans